Alegorisasi Hagar Sebagai Gunung Sinai dan Yerusalem dalam Penafsiran Paulus: The Allegorization Hagar's as Mount Sinai and Jerusalem in Paul's Interpretation - Yosua Sibarani (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
This article aims to explain the allegorization of Hagar and Mount Sinai in Paul's theology as written in Galatians 4:24-25 as a result of exegesis studies. To achieve this goal, the author uses a historical-grammatical approach. In addition, the author presents the interpretation debate by New Testament theologians about the text as consideration for deciding the interpretation following Paul's intent. In conclusion, Paul uses an allegorical interpretation of Galatians 4:24-25 by explaining that Hagar as Mount Sinai and Jerusalem is an allusion to the Old Testament and legalistic Judaism, not grace.